Numerical analysis of dialysis with chemical reaction at steady state. Irreversible second order reaction - Štěpánek Vojtěch; Palatý Zdeněk; Bendová Helena (Elsevier Science SA, 2015)
In the present work, the effect of chemical reaction on the rate of dialysis is analysed. The attention is paid to an irreversible second-order chemical reaction at steady state. A simple scheme, in which component A is transported through the membrane by diffusion and reacts with component B diffusing in the opposite direction, is considered. The analogy between the solution-diffusion model in the membrane transport and mass transfer in gas-liquid systems described by the film theory, both accompanied by chemical reactions, is taken into consideration. A numerical solution scheme is presented and the effect of chemical reaction is evaluated in terms of the enhancement factor for a wide range of parameters. The analysis of limiting cases is carried out and the applicability of the existing approximate solutions for the mass transfer accompanied by chemical reaction is examined. An effort was made to develop new correlations for the enhancement factor in the case that no approximate solution is available in literature.
Numerická analýza dialýzy s chemickou reakcí za ustáleného stavu. Irreverzibilní reakce druhého řádu.
Keywords: Dialysis; Mass transfer; Chemical reaction; Membrane; Enhancement factor; dialýza; transport hmoty; chemická reakce; membrána; reakční faktor